MANAJEMEN RESIKO PEMBIAYAAN DI BAITUL MAAL WA TAMWIL DAN BANK PEMBIAYAAN RAKYAT SYARIAH: SEBUAH STUDI PERBANDINGAN - Edi Susilo; Abdul Hakim (Faculty of Economics, Universitas Islam Indonesia, 2012)
This paper analyzes the impact of regulation and supervision system on the application of financial risk management in BMT Beringharjo (hereafter BMTB) and BPRS Madina (hereafter BPRSM). As understood, BMTs are loosely regulated and supervised by the Department of Cooperation, while BPRs are highly regulated and supervised by Bank Indonesia. Using a qualitative method, this paper finds that the financing organization in BMT needs improvement as the director and the manager are the same person. The financing procedure works well despite the lack of online system to coordinate branch offices. The paper also finds that BPRSM complies the financing procedure made by BI. The financing organization in BPRSM also works well, from the top commisariate to the employees level.